2019
DOI: 10.24252/bio.v7i2.6336
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of Epiphytic Moss in the Tree Trunk Zonation of Jumog Waterfall Ngargoyoso Tawangmangu Karanganyar Central Java

Abstract: The concept of epiphytic plants is a critical plant that determines the processes that occur in ecosystems. Epiphytic plants especially Bryophytes or commonly moss is one of primary productivity. This study aims to record any epiphytic moss in their natural habitat in the Jumog Waterfall Forest Ngargoyoso in Karanganyar Tawangmangu Central Java. The method used in this study was purposive sampling, this method using exploration techniques. Field data observed were epiphytic plants from the Bryophyte groups (mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…The species is widely distributed in tropical forests, dry forests, tropical savannas and coastal habitats in north-eastern Brazil. Previous studies revealed that O. albidum inhabits other urban areas in Indonesia, such as parking areas (Khujjah and Ekowati 2018), schoolyards (Aripulis 2019), and riparian vegetation (Roziaty et al 2019). The number of epiphytic bryophytes species obtained in this study was lower compared to Putrika et al (2017), who reported 36 species in the urban forest and the main road of the University of Indonesia's campus, Depok West Java, Indonesia.…”
Section: Composition and Diversity Of Epiphytic Bryophytesmentioning
confidence: 99%
“…The species is widely distributed in tropical forests, dry forests, tropical savannas and coastal habitats in north-eastern Brazil. Previous studies revealed that O. albidum inhabits other urban areas in Indonesia, such as parking areas (Khujjah and Ekowati 2018), schoolyards (Aripulis 2019), and riparian vegetation (Roziaty et al 2019). The number of epiphytic bryophytes species obtained in this study was lower compared to Putrika et al (2017), who reported 36 species in the urban forest and the main road of the University of Indonesia's campus, Depok West Java, Indonesia.…”
Section: Composition and Diversity Of Epiphytic Bryophytesmentioning
confidence: 99%